Growing Chlorella vulgaris in Photobioreactor by Continuous Process Using Concentrated Desalination: Effect of Dilution Rate on Biochemical Composition - Ângelo Paggi Matos; Regina Coeli de Oliveira Torres; Luiz Rodrigo Ito Morioka; Elisa Helena Siegel Moecke; Kepler Borges França; Ernani Sebastião Sant’Anna (International Journal of Chemical Engineering)
Desalination wastewater, which contains large amount of salt waste, might lead to severely environmental pollution. This study evaluated the effect of dilution rate (0.1≤D≤0.3 day−1) on microalgal biomass productivity, lipid content, and fatty acid profile under steady-state condition of Chlorella vulgaris supplemented with concentrated desalination. Continuous culture was conducted for 55 days. Results show that the biomass productivity (Px) varied from 57 to 126 mg L−1 d−1 (dry mass) when the dilution rate ranged from 0.1 to 0.3 day−1. At lowest dilution rate (D=0.1 day−1), the continuous culture regime ensured the highest values of maximum biomass concentration (Xm=570±20 mL−1) and protein content (52%). Biomass lipid content was an increasing function of D. The most abundant fatty acids were the palmitic (25.3±0.6%) at D=0.1 day−1 and the gamma-linolenic acid (23.5±0.1%) at D=0.3 day−1 ones. These fatty acids present 14 to 18 carbons in the carbon chain, being mainly saturated and polyunsaturated, respectively. Overall, the results show that continuous culture is a powerful tool to investigate the cell growth kinetics and physiological behaviors of the algae growing on desalination wastewater.